Construction Of Railway Door Automation Prototypes Using Arduino, Servo Motors and Ultrasonic Sensors : Konstruksi Prototipe Otomatisasi Pintu Kereta Api Menggunakan Arduino, Motor Servo, dan Sensor Ultrasonik - Kharisma, Ivana Lucia; Kamdan; Firdaus, Asep Rizki; Prayoga , Rizki Haddi; Yasin, Fakhriyal Riyandi; Tresna Ati, Mutiara Annisa (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2023)
The Indonesian railway system is currently experiencing a lot of developments in terms of technology. The Indonesian railway system has been integrated with technology 4.0, where all transaction processes, whether payment, ordering tickets or monitoring trains, can be monitored via electronic media. Of course, this technology must be supported by adequate infrastructure, one of which is the railroad crossing. In Indonesia, several railroad lines have been constructed, and many portal or crossbar railroads have also been constructed. The railroad gate is part of the railway system which has a very important role, especially in regulating the safety of train travel. The rail gateway has been a problem and a source of accidents in recent years. This is because there are no security facilities at any rail portals, causing drivers to continue to break traffic laws. The making of this automatic railroad doorstop uses the Prototype method, namely a simulation that uses Arduino UNO R3, servo motors, HC-SR04 ultrasonic sensors and other components that can support the manufacture of this railroad doorstop prototype. The prototype of this automatic train doorstop is equipped with many sensors that works automatically according to what is ordered, so that its use can be easily controlled and implemented in real life. This automatic railroad crossing system is expected to optimize the task of the railroad crossing guard by providing automation for the process of opening and closing the railway door and providing additional warning information for the community around the railway door location so as to reduce the potential for accidents caused by drivers or people who break traffic laws.